Combined Fourier-transform infrared imaging and desorption electrospray-ionization linear ion-trap mass spectrometry for analysis of counterfeit antimalarial tablets. - Ricci, C; Nyadong, L; Fernandez, F; Newton, P; Kazarian, S (2007)
This paper reports use of a combination of Fourier-transform infrared (FTIR) spectroscopic imaging and desorption electrospray ionization linear ion-trap mass spectrometry (DESI MS) for characterization of counterfeit pharmaceutical tablets. The counterfeit artesunate antimalarial tablets were analyzed by both techniques. The results obtained revealed the ability of FTIR imaging in non-destructive micro-attenuated total reflection (ATR) mode to detect the distribution of all components in the tablet, the identities of which were confirmed by DESI MS. Chemical images of the tablets were obtained with high spatial resolution. The FTIR spectroscopic imaging method affords inherent chemical specificity with rapid acquisition of data. DESI MS enables high-sensitivity detection of trace organic compounds. Combination of these two orthogonal surface-characterization methods has great potential for detection and analysis of counterfeit tablets in the open air and without sample preparation.